Chloroplast protease/chaperone AtDeg2 holds γ1 subunit of ATP synthase in an unaggregated state under high irradiance conditions in Arabidopsis thaliana - Jagodzik, P; Jackowski, G (Photosynthetica, 2022)
Little data on the role played in vivo by chloroplast protein AtDeg2 as a chaperone is available. Therefore, we sought for chloroplast proteins protected from high irradiance-induced interprotein aggregation via disulphide bridges by AtDeg2 acting as a holdase. To reach this goal, we performed analyses which involved comparative diagonal electrophoreses of lysates of chloroplasts isolated from wild type (WT) plants and transgenic plants 35S:AtDEG2ΔPDZ1-GFP which expressed AtDeg2 lacking its chaperone activity but retaining the protease activity. The results of the analyses indicate that AtDeg2 acting as a holdase prevents a single chloroplast protein, i.e., the γ1 subunit of ATP synthase from long-term high irradiance-induced homodimerization mediated by disuplhide bridges and this allows us to better understand a complexity of physiological significance of AtDeg2 - the chloroplast protein of dual protease/chaperone activity.
Keywords: elevated irradiance; protease; Deg2; chaperone; homodimerization